PERANCANGAN PERANCANGAN PIT PENAMBANGAN BLOK 1 SECARA SHORT TERM PADA PT HARVEST CONTRUCTION MINING COMPANY - Ma'ruf, Baso Amran; Anwar, Habibie; Nurwaskito, Arif (CV Insight Publisher, 2023)
This research was conducted at PT Harvest Construction Mining Services which is engaged in mining, especially in nickel ore mining as a mining consultant. Which is located in Mandiodo Village, Mandiodo District, North Konawe Regency, Southeast Sulawesi. This study aims to create a pit design and mining sequence design at PT Harvest Construction Mining Services, to make a production schedule based on daily ore production targets. Based on the results of the research, the pit limit was designed based on the estimation results of the block model with the parameters of bench height of 5 m, width of berm 2 m, CoG of 1.5%, and a minimum stripping ratio value of 1:3. Based on the pit limit design, the opening volume is 371,445 m3. Based on the mining pit limit, the pit limit design is divided into several smaller units using mining software. The results of the analysis of the distribution of mining sequences obtained four mining periods with each period per quarter. The first mining sequence obtained a total ore of 67,215 tons of overburden 104.383 tons, the second sequence obtained a total of 71,814 tons of ore with 39,081 tons of overburden, the third sequence with 72,735 tons of ore and 40,547 tons of overburden. The fourth sequence, which is the pit limit of mining, obtained a total of 67,033 tons of ore with a total overburden of 110,100 tons. The total ore to be mined is 278,797 tons.